2018
DOI: 10.1002/jmri.26250
|View full text |Cite
|
Sign up to set email alerts
|

3D MR Elastography of Hepatocellular Carcinomas as a Potential Biomarker for Predicting Tumor Recurrence

Abstract: 4 Technical Efficacy: Stage 5 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Magnetic resonance elastography can predict the development of hepatocellular carcinoma: a meta-analysis and systematic review of clinical treatment methods as well as the assessment of prognosis (12)(13)(14)(15).…”
Section: Original Articlementioning
confidence: 99%
“…Magnetic resonance elastography can predict the development of hepatocellular carcinoma: a meta-analysis and systematic review of clinical treatment methods as well as the assessment of prognosis (12)(13)(14)(15).…”
Section: Original Articlementioning
confidence: 99%
“…For every 1 kPa increase in tumor stiffness, the risk of tumor recurrence increased by 16.3%. The relapsed HCC has higher tumor stiffness ( 49 ). Liver stiffness measured by MRE can also be used as a prognostic indicator for HCC patients undergoing hepatectomy.…”
Section: Application Of Mre In Tumor Diagnosis and Treatmentmentioning
confidence: 99%
“…Other authors using radiomics on pre-operative CT-scans found a good correlation with MVI (AUC 0.80) [74] . Beyond texture, using 3D MRI was also possible to evaluate tissue stiffness; a multicenter study [75] recently found that HCCs with subsequent recurrence had higher tumor stiffness.…”
Section: Imaging Predictive Factorsmentioning
confidence: 99%